IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI DESA AKO KECAMATAN PASANGKAYU KABUPATEN MAMUJU UTARA - Wahyuddin, Wahyuddin (Katalogis, 2016)
This Research aim to to know Implementation Policy Of Allocation Fund Countryside [in] Countryside of Ako District Of Pasangkayu Sub-Province of Mamuju. Especial Theory [of] policy implementation taken as reference [is] Edwards III including; (1) communications, (2) resource, (3) disposition, (4) bureaucracy structure. Research method use descriptive approach qualitative. Research place [in] Countryside of Ako District Of Pasangkayu Sub-Province of Mamuju North with informan 10 one who [is] selected by purposive, data collecting by interview, observation, and documentation. Technique analyse data use model of interaktif Miles and of Huberman. Pursuant to result of research that implementation policy of countryside fund alokadi [in] Countryside of Ako District of Pasangkayu if seen from aspect ( 1) communications, (2) resource, (3) disposition, (4) bureaucracy structure result of research prove that implementation policy of countryside fund allocation [in] Countryside of Ako District of its Pasangkayu result not yet is optimal, like: (1) communications to socialize to policy of countryside fund allocation to society there is no, (2) still lower him knowledge of countryside aparatur and lack of support of finansial in execution of policy, (3) lack of respon [all] executor of countryside fund allocation assuming policy of countryside fund allocation [is] a policy of mere routine, (4) resistor factor in bureaucracy structure [is] there is no him of[is division of duty among team organizer of activity and lack of team coordination organizer of activity of countryside fund allocation